Emerging hot spot analysis to indicate forest conservation priorities and efficacy on regional to continental scales: a study of forest change in Selva Maya 2000–2020. (1st July 2022) - Cuba, Nicholas; Sauls, Laura A; Bebbington, Anthony J; Bebbington, Denise Humphreys; Chicchon, Avecita; Marimón, Pilar Delpino; Diaz, Oscar; Hecht, Susanna; Kandel, Susan; Osborne, Tracey; Ray, Rebecca; Rivera, Madelyn; et al.
Abstract: Despite the importance of preserving contiguous tropical forest areas to maintain biodiversity and terrestrial carbon stocks, methodological challenges continue to hinder broad-scale analysis of threats to these forests. Emerging Hot Spot Analysis (EHSA) is a spatial-statistical method that conveys complex information about the temporal dynamics of deforestation across a range of moderate to coarse spatial scales. Using Global Forest Change (GFC) data as inputs, EHSA produces spatially comprehensive, gridded outputs that represent a standardized, reproduceable way to instantiate contiguous forest tracts as spatial objects. Doing so allows aggregation of other GFC-derived values and analysis of alternative geographic configurations besides sub-national jurisdictions or protected areas, which can limit observation of finer scale variations. This paper illustrates the method's utility to comprehensively characterize the magnitude and temporality of pressures facing the Selva Maya, a transboundary forest region with extensive areas under conservation that covers portions of Mexico, Guatemala, and Belize.